Exploring a synergistic-type magnetostructural transformation in Ni-Mn-Ga-X (X = Sn, Sb) Heusler alloys. (September 2021) - Li, Fan; Su, Mengyao; Zhao, Dewei; Liu, Jian; Sun, Qisong; Ma, Li; Zhen, Congmian; Hou, Denglu
Abstract: In this paper, the magnetostructural transformation from paramagnetic austenite to ferromagnetic martensite is described as a synergistic-type phase transformation because the structural and magnetic subsystems exhibit two unique synergistic effects: (1) lattice vibration and magnetic entropy changes synergistically contribute to the total entropy change; (2) the structure and magnetism synergistically response to external cross-fields. Such synergistic-type phase transformation has been explored in Ni-Mn-Ga-X (X = Sn, Sb) Heusler alloys. By the substitution of Sn/Sb for Ga, a temperature window of 50 K for the synergistic-type phase transformation has been established in the phase diagram of Ni-Mn-Ga-X (X = Sn, Sb). Associated with the synergistic contribution of lattice vibration and magnetic entropy changes, the samples exhibit high phase transformation entropy changes (≥1.2 J/molK) within the temperature window. The synergistic effects of the magnetostructural transformation make the Ni-Mn-Ga-X (X = Sn, Sb) alloys to be potential multicaloric materials. Highlights: A synergistic-type magnetostructural transformation has been explored in Ni-Mn-Ga-X (X = Sn, Sb) alloys. A temperature window of 50 K for the synergistic-type  magnetostructural transformation has been established. The samples exhibit high phase transformation entropy changes (≥1.2 J/molK) within the temperature window.